The Effect of Product Innovation, Price, and Product Quality on Consumer Satisfaction with OMG Products - Nasution, Pebriyana; Maharani, Nabila Putri (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth as public awareness of beauty and personal care increases. One of the emerging brands in this market is Oh My Glam (OMG), which offers high-quality products at affordable prices while continuously innovating to follow global beauty trends. In a highly competitive market, product innovation, pricing strategies, and product quality are key to determining consumer satisfaction. This study investigates the impact of product innovation, pricing, and product quality on consumer satisfaction with OMG products. A quantitative approach was utilized through a survey method, with data collected via an online questionnaire using a Likert scale. The results show that product innovation, pricing, and quality positively affect consumer satisfaction. Product innovation enhances appeal and perceived value, competitive pricing boosts satisfaction, and product quality is essential in strengthening customer loyalty. The limitation of this study lies in the sample scope, which only includes OMG consumers in Bandar Lampung. Therefore, the findings cannot be widely generalized to other cosmetic brands.